The Position of Self-Employed Farmers in the Business Environment - Žuffová Eva (EU agrarian Law)
The position of self-employed farmers (SEF) in the business environment is a topical issue, as self-employed farmers play a key role in the agricultural sector and in rural development as well. Independent farmers often operate as small and family farms, contributing to the economic stability and food security of the regions in which they operate. However, their position in the business environment is influenced by factors such as legislative conditions, access to financial resources, the number of market opportunities, and support mechanisms from the state or the European Union. The main goal of the paper is to describe the position of the self-employed farmer and his role in rural development. In the contribution, we are devoted to the legislative definition of the legal form of independent farming of a farmer, which defines the main advantages and disadvantages of this type of business. In the next part of the post, we are devoted to the development of the number of SEF in Slovakia, where we record the number of these entities over a long period of time. In the end, we provide an overview of financial support options for self-employed farmers. For the future of the Slovak countryside and agriculture, it is crucial to constantly support young and small farmers and create conditions for their growth and development